Legal Urgency in the Establishment of the AntiCorruption Corps in the Indonesian National Army - Raditya Feda Rifandhana; Bambang Angkoso Wahyono; Syahdina Yahwa; Mochamad Ardiyanto; Rafa Huwaida (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Corruption in legal thought, part of the extraordinary crime, the extraordinary crime, is categorized as a crime that can enter any agency, both civilian and military, so that this extraordinary crime damages the order of norms, even the organs that have been arranged by legal norms. In this study, it discusses the legal vacuum, the formation of new organs, even the urgent necessity needed for the formation of norms in the formation of new organs and even laws and regulations, legal urgency is a legal imperative in the formation of anti-corruption organs in the National Army of the Republic of Indonesia carried out by stakeholders, Legislative, Executive, Judiciary and even Military in a progressive, responsive manner. The Military Discipline Law, the Corruption Crime Law, is packaged in normative research.